Association of genetic ancestry with striatal dopamine D2/D3 receptor availability. Issue 8 (August 2018) - Wiers, C; Towb, P; Hodgkinson, C; Shen, P-H; Freeman, C; Miller, G; Lindgren, E; Shokri-Kojori, E; Demiral, Ş; Kim, S; Tomasi, D; Sun, H; et al.
Abstract Despite ethnic differences in allele frequencies of variants in dopaminergic genes associated with dopamine D2/D3 receptor availability (D2R), no study to date has investigated the relationship between genetic ancestry and striatal D2R. Here, we show that ancestry-informative markers significantly predict dorsal striatal D2R in 117 healthy ethnically diverse residents of the New York metropolitan area using Positron Emission Tomography (PET) with [11 C]raclopride (P <0.0001), while correcting for age, sex, BMI, education, smoking status, and estimated socioeconomic status (ZIP codes). Effects of ethnicity on D2R were not driven by variation in dopaminergic candidate genes. Instead, candidate gene associations with striatal D2R were diminished when correcting for ancestry. These findings imply that future studies investigating D2 receptor genes should covary for genetic ancestry or study homogeneous populations. Moreover, ancestry studies on human neurobiology should control for socioeconomic differences between ethnic groups.